Confinement of Ultrasmall Bimetallic Nanoparticles in Conductive Metal–Organic Frameworks via Site‐Specific Nucleation (Adv. Mater. 38/2021). Issue 38 (21st September 2021) - Park, Chungseong; Koo, Won‐Tae; Chong, Sanggyu; Shin, Hamin; Kim, Yoon Hwa; Cho, Hee‐Jin; Jang, Ji‐Soo; Kim, Dong‐Ha; Lee, Jiyoung; Park, Seyeon; Ko, Jaehyun; Kim, Jihan; et al.
Abstract : NO2 Sensors In article number 2101216, Il‐Doo Kim and co‐workers demonstrate a conductive metal–organic framework (cMOF) with enhanced activity owing to encapsulation of ultrasmall bimetallic nanoparticles (BNPs) within the cMOF matrix. The combination of the high surface area of the cMOF and the bimetallic synergies of the PtRu BNPs enables application as a highly sensitive chemiresistive sensor toward NO2 detection.